Health care management practices followed by dairy animal owners in tribal areas of Gujarat (Indian Journal of Animal Production and Management, 2024)
Afield survey was conducted to ascertain the health care management practices followed by dairy animals owners in Valsad district of South Gujarat and data were collected from randomly selected two talukas and 240 respondents through personal interview with the help of structured interview schedule. The present study revealed that majority of respondents (85%) practiced regular vaccination to their animals against F.M.D. and H.S. disease. Only 35.4% of respondents practiced deworming of their dairy animals regularly and 70.8% respondents followed various practices for control of ecto–parasites.About 55.8% of respondents had cleaned animal sheds and only 13.8% of the respondents were treated their sick animals by qualified veterinarians. Majority (99.2%) of respondents washed the animal’s hind quarters after drop of placenta. About 99.2% respondents did not follow grooming practice for their dairy animals and 97.1% respondents kept diseased animals together with healthy ones in a shed.
Keywords: Dairy animals; Health care; Management; Practices; Tribal area